Effectiveness Problem Based Learning with Teaching at the Right Level Approach on Learning Outcomes and Group Discussion Skills of Environmental Change Material for Class X Students of SMAN 1 Jember - Ainur Rofiqi; Suratno Suratno; Yeni Vida Ervina (INKUIRI: Jurnal Pendidikan IPA, 2024)
This study aims to determine the effectiveness of Problem-based Learning with Teaching at the Right Level approach on learning outcomes and group discussion skills of environmental change material for class X6 SMAN 1 Jember. This research included Classroom Action Research (CAR) which was carried out in 2 cycles. The research design used has a cyclical form that refers to the Kemmis & Taggart model with four main activities, namely planning, acting, observing, and reflecting. The data collection of learning outcomes was carried out through post tests while group discussion skill data was carried out through observation to students referring to Greenstein indicators. The results showed an increase in learning outcomes and discussion skills in cycle 2 with a percentage of classical completeness of 91.67% and an average group discussion skill of 85.67% with a very good category.